lncNBAT1/APOBEC3A is a mediator of HBX-induced chemoresistance in diffuse large B cell lymphoma cells - Jianguo Li; Yaqi Chen; Xuecong Guo; Xiaofei Bai; Xu Xu; Tong Han; Ailing Tan; Nana Liu; Yuchen Xia; Qiaoyi Sun; Xudong Guo; Jie Chen; et al. (Elsevier, 2022)
Individuals with diffuse large B cell lymphoma (DLBCL) infected with hepatitis B virus (HBV) have worse chemotherapy efficacy and poorer outcomes. It is still unclear whether long noncoding RNAs (lncRNAs) serve as prognostic and therapeutic targets in the chemotherapy resistance of individuals with DLBCL and HBV infection. Here we found that the core component of HBV (HBX) directly upregulated the expression of lncNBAT1, which was closely associated with the chemotherapy outcomes of HBV-infected individuals with DLBCL. Upregulation of lncNBAT1 reduced the sensitivity of DLBCL cells to chemotherapeutic agents (methotrexate [MTX] or cytarabine [Ara-C]) that induced S phase arrest, whereas knockdown of lncNBAT1 significantly relieved the chemoresistance of HBX-expressing DLBCLs. Mechanistically, lncNBAT1 could interact with the signal transducer and activator of transcription 1 (STAT1) to prevent its enrichment at the promoter region of the functional target gene apolipoprotein B mRNA editing enzyme catalytic subunit 3A (APOBEC3A), inhibiting expression of APOBEC3A and inducing resistance to MTX in DLBCL cells. Furthermore, clinical data analysis showed that lncNBAT1 and APOBEC3A expression was closely related to the poor prognosis and short survival of individuals with DLBCL. Our findings suggest a potential prognostic marker and a candidate lncRNA target for treating HBV-infected individuals with DLBCL.